Development of a flipbook-based e-module using case study method in applied physics for civil engineering at Politeknik Negeri Nunukan - Rahmawati, Lusy; Anggini, Canda Putri; Syarifudin, Syarifudin; Anandita, Aulia Silvina; Utami, Vina Bekti (Universitas Muhammadiyah Mataram, 2025)
This study aims to develop and assess the feasibility of a flipbook-based e-module using the case study method for the Applied Physics course in the Civil Engineering for Urban Infrastructure Study Program at Politeknik Negeri Nunukan. The motivation behind this development stems from the absence of structured and contextual learning materials aligned with the 7th Main Performance Indicator (IKU 7), which emphasizes collaborative and participatory learning through project or case-based approaches. The research employed a Research and Development (R&D) approach using the 4D model Define, Design, Develop, and Disseminate although this study was limited to the Develop stage. Validation was carried out by material and media experts, while student feedback was gathered from a limited trial involving 22 first-semester students. The results of expert validation yielded an average score of 3.63 (91%), and student responses showed a mean score of 3.50 (88%), both categorized as